Anomalous susceptibility in single crystals of EuCo2Si2 with trivalent Eu: Influence of excited J multiplets. Issue 3 (18th February 2013) - Seiro, Silvia; Kummer, Kurt; Vyalikh, Denis; Caroca‐Canales, Nubia; Geibel, Christoph
Abstract We present a detailed study on the physical properties of single crystals of the Eu3+ intermetallic EuCo2Si2. The Eu valence was confirmed by X‐ray absorption. At low temperatures, the anisotropic susceptibility can be explained by a Eu3+ Van Vleck contribution with a crystal field parameter <![CDATA[$V_{2}^{0} = 355\, {\rm K}$]]> <inline-graphic xlink:href="ark:/27927/pgg1v77rf6h" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />, but at high temperatures the data exceed the Van Vleck values significantly. This excess susceptibility is possibly related to the magnetic exchange between the excited Eu multiplets and the conduction band. A γ of 9.6 mJ K−2 mol and a Debye temperature of 322 K were estimated from the low temperature specific heat data. The compound does not undergo any phase transition in the temperature range 2–300 K.